Analisis Kelayakan Investasi Pengadaan Alat Angkut Material untuk Meminimalkan Biaya Logistik (Studi Kasus: PT. Tiki Cabang Solo) - Ika Shinta M.; Nabila Nur F.; Christian A. W. (Performa: Media Ilmiah Teknik Industri, 2016)
Abstract—Management of goods in logistics company is required till deliver the goods quickly and accurately, thus it can improve additional value and can compete with other competitors. But, in fact there are many factors that cause delivery delay. It is experienced by PT. TIKI Branch Solo which has a delay in the delivery of goods from the station to the airport. By fishbone diagram, the main cause is the current method of loading/unloading from truck to the station and vice versa it uses manual handling. Then, it affects to the productivity in terms of time and costs. So, the solution is considered such as forklift and trolley to speed up the process of loading/unloading. Both alternatives compared with manual system use financially and technically process. Based on financial result, trolley is the most effective alternative from the value of Manual Handling Costs is Rp 6.946,67 and Nett Present Value is Rp 43.752.394,91. Technically, trolley is faster than others as goods movement process can be done effectively and efficiently. Finally, it can solve the problem of delivery delay in PT. TIKI Branch Solo.